3D Printing Flexible Sodium‐Ion Microbatteries with Ultrahigh Areal Capacity and Robust Rate Capability (Adv. Mater. 39/2022). Issue 39 (27th September 2022) - Ma, Jiaxin; Zheng, Shuanghao; Chi, Liping; Liu, Yu; Zhang, Ying; Wang, Kai; Wu, Zhong‐Shuai
Abstract : 3D‐Printed Microbatteries In article number 2205569, Shuanghao Zheng, Zhong‐Shuai Wu, and co‐workers report a prototype of a planar and flexible 3D‐printed sodium‐ion microbattery with a 3D hierarchically porous framework by consecutively printing cathode, anode, and electrolyte inks. Such a printable strategy paves a new avenue for scalable and customizable fabrication of high‐energy micro‐power‐sources for next‐generation wearable and portable microelectronics.